ROLE OF IMPORTS TO BUILDING IN INDONESIA - Hasibuan, Andriansyah; Saajidah, Annisa; Aini, Lathifa; Runi, Naila Ananda (Universitas Negeri Medan, 2023)
The purpose of this research is to know the role of imports in development in Indonesia, the research methods in this research are the library study method, the data collection technique used is secondary data with content analysis techniques. Import activities have a complex impact on human resources in Indonesia. On the one hand, imports can create new jobs for Indonesian people, especially in the distribution and trade sectors, but on the other hand, they can also threaten jobs in manufacturing and agriculture, where local production can compete less with cheaper imports, and import activities can have a positive and negative impact on poverty in Indonesia. The results of this study show that importing activities tend to have a negative impact on natural resources, i.e. they can reduce the sustainability of living resources, they can affect mineral resource sustainability, and they affect forest resources sustainability and reduce forest resource reserves. Import activities have a positive and a negative impact on poverty in Indonesia.The positive impact can occur when imports are used to meet the needs of raw materials or capital goods that are not available in the country, while the negative impact can lead to a reduction in employment and income for the people.